Sudden collapse of steel water tower tank due to compound openings in critical zone. Issue 1 (31st December 2023) - Zaki, Rana I. K.; Risan, Hussam K.; Mohammed, Ramzi Q.
Abstract: Despite previous efforts to detect concentrated stresses in structures with holes, a complete understanding of structures that contain compound openings in addition to screw holes in critical stress areas is incomplete, especially for structures that are subject to sudden collapse. This study aims to conduct a laboratory test program to simulate a suddenly collapsed tank that contains compound holes in addition to the screw holes distributed on the cleaning opening located in the critical stress area. Six laboratory simulated models with two repeats for each are tested to represent the stages of implementation of the cleanout opening and to find out the causes of the sudden failure of the tank. Significant reduction in resistance when having a centre hole compared to the control plate. The importance of the stiffeners is evident in this region, as the resistance decreased slightly compared to the control plate by adding reinforcement plates on both sides. The resistance drop remains almost constant despite the stiffening panels being punctured on both sides with the same diameter as the main hole, which confirms the continued importance of the stiffeners at this stage. An improvement in resistance was observed when a cap was added to one of the holes in the stiffeners. A slight change in resistance was also observed when the cap was pierced with another hole to weld the cleaning pipe due to the failure remaining within the screw holes surrounding the main hole. In conclusion, the safety factor should be increased in areas that contain compound openings.